4g+3(-6+3g)=1-g

Simple and best practice solution for 4g+3(-6+3g)=1-g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4g+3(-6+3g)=1-g equation:


Simplifying
4g + 3(-6 + 3g) = 1 + -1g
4g + (-6 * 3 + 3g * 3) = 1 + -1g
4g + (-18 + 9g) = 1 + -1g

Reorder the terms:
-18 + 4g + 9g = 1 + -1g

Combine like terms: 4g + 9g = 13g
-18 + 13g = 1 + -1g

Solving
-18 + 13g = 1 + -1g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add 'g' to each side of the equation.
-18 + 13g + g = 1 + -1g + g

Combine like terms: 13g + g = 14g
-18 + 14g = 1 + -1g + g

Combine like terms: -1g + g = 0
-18 + 14g = 1 + 0
-18 + 14g = 1

Add '18' to each side of the equation.
-18 + 18 + 14g = 1 + 18

Combine like terms: -18 + 18 = 0
0 + 14g = 1 + 18
14g = 1 + 18

Combine like terms: 1 + 18 = 19
14g = 19

Divide each side by '14'.
g = 1.357142857

Simplifying
g = 1.357142857

See similar equations:

| p-42=-42 | | -7x-2=-5x+6 | | (x^2+25)(x^2-9)=0 | | -4(-C-16)=-4-16 | | 0=t*lnt | | C=0.5x+22.4 | | 9y-5=23+2y | | 8(x+3)=38 | | 0.5x+9=-4 | | 9p-19=-61+2p | | x^2=-3x+9x | | 2(x-7)+3-5x=23 | | -3+p/6=-5 | | -6.9x+23.3831=-1.1(x-4.237) | | (-2+-2y)+3y=-4 | | 4+11x=7x-1 | | 7x+23x-5=6(5x+8) | | 10x-9=-11 | | 936-(x+24)=72 | | 4x-4+2y=0 | | (9-r)3-12r=33 | | 2(4s+5)-4s=2(2s+4)-9 | | 100y+20x+100= | | 3(x-5)=5(x+5) | | C=0.5x+8x+4000 | | -j+-13j= | | 7-7n+5n=16-55 | | x+(-19)=31 | | (7x+5)+(4x+2)= | | 4(2y-2)=24 | | -5(n-1)-6n=-6(n+4)-1 | | 2r-(5-r)=13*2r |

Equations solver categories